A laboratory behavioral assessment on predatory potential of the green lacewing Mallada basalis walker (Neuroptera: chrysopidae) on two species of papaya pest mites, Tetranychus kanzawai Kishida and Panonychus citri (McGregor) (Acari: tetranychidae) - Cheng, Ling-Lan (Kansas State University, 2007)
Tetranychus kanzawai Kishida and Panonychus citri (McGregor) are the two major arachnid pests of screenhouse-cultivated papayas in Taiwan. Control of these mites has become more difficult because both pests have become resistant to most registered miticides. This laboratory study investigated the feeding behaviors, predatory potential, and prey preference of a domesticated line of Mallada basalis Walker, a commonly-occurring chrysopid in Taiwan, to both of these pest mites. A laboratory assessment on control efficacies of different predator:prey release ratios to single and mixed-pest species was also conducted. Behavioral study showed that all larval stages of M. basalis exhibited a high rate of acceptance of all life stages of both T. kanzawai and P. citri. Second and third instar predators foraged actively during most of the 2-h tests. Numbers and rates of prey consumption were measured for each instar of predator and prey. Results showed that consumption increased and prey handling time decreased as predator life stage advanced, and prey stage decreased. Mallada basalis exhibited both a shorter handling time and corresponding higher consumption rate on P. citri compared with T. kanzawai. Handling time and consumption rate also were positively affected by increasing prey density. Mallada basalis did not exhibit notable species or life stage preferences, and prior feeding experience on one mite species did not affect subsequent prey choice between the two mites. Lacewings significantly reduced T. kanzawai and P. citri populations at a predator:prey ratio of 1:30 and this improved at ratios of 1:15 and 1:10. Control of T. kanzawai was slightly better than P. citri when the mites occurred singly and together. Consumption by M. basalis increased with temperature up to 30C. I conclude that M. basalis has high potential for augmentative biological control of papaya mites. Further field investigations are needed for making final recommendations.
Keywords: Biological control; Green lacewings; Foraging behavior; Prey preference; Temperature effect; Biology, Entomology (0353)